AN ANALYSIS OF THE CONFLICTS OF THE MAIN CHARACTER'S AND THE PLOT STRUCTURE IN THE "DO REVENGE" (2022) (The GIST, 2024)
This study aims to understand how conflicts build the plot in the film "Do Revenge." Using Freytag's plot theory, this research identifies the stages of plot development driven by the conflicts experienced by the main character. The findings demonstrate that both internal and external conflicts play a significant role in shaping the narrative structure and character development. These conflicts not only add tension and drama to the story but also help guide the plot towards its climax and resolution. Thus, this study provides a deeper insight into how conflicts are utilized as essential narrative elements in building the plot and developing characters in the film "Do Revenge." It also highlights how the film's writers and directors use conflicts to reinforce the message they aim to convey to the audience.